Comparisons Between Alate Aphids Caught in Υellow Water Traps and Aphid Populations on Tomato Plants - Lykouressis, D. P.; Perdikis, D. CH.; Chalkia, CH.A.; Vardaki, S. C. (ENTOMOLOGIA HELLENICA, 1993)
Aphid monitoring was conducted by means of yellow Moericke water traps placed in tomato fields in two different localities in Co Boiotia during the growing seasons in 1992 and 1993. Additionally, aphid population densities were estimated by plant sampling. Macrosiphum euphorbiae (Thomas) and Myzus persicae (Sulzer) were the only species which developed populations on plants. Regression analysis between the number of alates from traps with either the number of alates or the total aphid population on plants showed that there was no correlation in the case of M. persicae for both localities and years. However, there were significant relationships between the number of alates in traps and either the number of alates on plants (r2=0.83) or the total aphid population on plants (r2=0.69) for M. euphorbiae in 1992. In 1993, such significant relationships were not found for the latter species, most probably due to extremely low trap catches. Significant relationships were also found between alates in traps, during their immigration period, with either alates on plants (r2=0.93) or the total population on plants (r2=0.80) in M. euphorbiae in 1992.